Caracterização química e estoque de carbono no solo sob agroecossistemas e mata nativa - Rufino , Dayseana Carneiro (2018)
Replacement of vegetation cover and inadequate soil management alter soil incoming and outflow of nutrients. In this sense, two experiments were conducted; in the first one, the fertility components at different depths were evaluated under agroecosystems in comparison with secondary vegetation area in the municipality of Remígio-PB; in the second, in the same areas, depths and agroecosystems the carbon stock was qualified. The work was carried out in the localities of Caiana and Mata Redonda, belonging to the municipality of Remígio - PB, located in the mesoregion of the Paraíba agreste, Curimataú Microregion. Four areas were selected, characterized according to the cultivation system: conventional system, pasture, agroforestry system (SAF) and an area with secondary vegetation. Soil samples were collected from July to August / 2017 for chemical evaluation at the Soil Laboratory of the Federal University of Paraíba (UFPB), Campus III, Bananeiras, PB, at the Center for Human, Social and Agricultural Sciences (CCHSA). The studied variables were analyzed using the statistical model, in a completely randomized design, in a factorial arrangement [(3x3)+1], being the factors: cultivation system (conventional, pasture and agroforestry system), depth (0-20; 20-40 and 40-60 cm) and an additional treatment corresponding to secondary vegetation. The variables, in the first experiment, were studied for the active acidity by pH in H2O (1: 2,5) organic carbon (CO), available phosphorus (P), exchangeable contents of (Ca2+, Mg2+ and K+), exchangeable aluminum (Al3+) and potential acidity (H+ + Al3+). The sum of bases (SB), cation exchange capacity (CTC), base saturation (V%) and aluminum saturation (m%) were obtained. In the second experiment, besides those variables described above, the soil carbon stock (ECS) was obtained. In the first, the area with secondary vegetation had higher levels of organic matter, regardless of the depth in comparison to the agroecosystems in cultivation; (0-20 cm) presented in all areas the highest levels of organic matter and nutrient, with a decrease in depth. The aluminum contents increased with soil depth. In the second experiment, the cropping systems caused alterations in the chemical characteristics of the soil when compared to the preserved conditions of secondary vegetation and the soil carbon stock was higher in the superficial layer (0-20 cm) and in the environments where the characteristics are closer those of balance, describing in depth.